Busca por novos metalofármacos contra doenças negligenciadas (malária, doença de chagas e leishmaniose) - Barbosa, Marília Imaculada Frazão (2012)
Leishmaniasis, Chagas disease and malaria are neglected parasitic diseases responsible for high mortality in tropical low-income countries. Due to the lack of vaccines and of safe, effective and affordable treatments, there is an urgent need to reinforce the existing therapeutic arsenal against these diseases. Many potential drugs have been investigated for these diseases, including ruthenium complexes. Ruthenium complexes are very appreciated in medicinal chemistry due to the tendency to be selective to bind biomolecules, which partly accounts for the low toxicity. Thus, in this work were synthesized and characterized ruthenium complexes with ligands that have antiparasitic activity recognized as lapachol and chloroquine diphosphate, bioactive ligands such as nitric oxide and amino acids. The compounds were characterized by elemental analysis techniques, absorption spectroscopy ultraviolet visible, infrared, nuclear magnetic resonance 31P {1H}, 13C, 1H and COSY, paramagnetic resonance spectroscopy and X-ray diffraction.The complexes showed promising results against diseases evaluated (malaria, leishmaniasis, Chagas disease and tuberculosis) showing that coordination leads to the synthesis of complexes most active against the parasites and less toxicity in healthy cells.